Metaphor in Scientific Communication - Štambuk, Anuška (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1998)
AbstractWhen communicating new knowledge we often use metaphors that provide understanding of one kind of experience by relating it to another. Apart from their use in basic linguistic communication, metaphorical models play an important part in communicating new discoveries in scientific theories. They also shape our experience and affect our picture of the world. The imaginative description of conceptual relations stimulates the research process, providing the basis for new discoveries.